2021
DOI: 10.3389/fnhum.2021.654610
|View full text |Cite
|
Sign up to set email alerts
|

Imagining How Lines Were Drawn: The Appreciation of Calligraphy and the Facilitative Factor Based on the Viewer’s Rating and Heart Rate

Abstract: For this study, we examined how recognizing the writing process of calligraphy influences the cognitive and affective processes related to appreciating it, with the aim of contributing to both graphonomics and the psychology of aesthetics. To this end, we conducted two Web-based experiments in which some participants were instructed to view calligraphy by tracing it with their eyes (the tracing method), while others were told to feel free to think and imagine whatever they wanted. Study 1 (N = 103) revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The first finding revealed that the presence or absence of creation did not influence later evaluation, which may be attributed to the difference in art genres. Prior studies have suggested that tracing the creative process, rather than the creation itself, influences subsequent evaluation (Matsumoto & Okada, 2021a, 2021b). In other words, it is believed that all Japanese have experienced creating haiku (Uesaka & Koushima, 2013) and that it is possible to trace its creative process without having created it before.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first finding revealed that the presence or absence of creation did not influence later evaluation, which may be attributed to the difference in art genres. Prior studies have suggested that tracing the creative process, rather than the creation itself, influences subsequent evaluation (Matsumoto & Okada, 2021a, 2021b). In other words, it is believed that all Japanese have experienced creating haiku (Uesaka & Koushima, 2013) and that it is possible to trace its creative process without having created it before.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have suggested that tracing the creative process, rather than the creation itself, in uences subsequent evaluation. [10,20] In other words, it is believed that all Japanese have experienced creating haiku and that it is possible to trace its creative process without having created it before. Considering that linguistic art, especially haiku, relies on mental images (Hitsuwari & Nomura, 2022a), it would be easier to trace the creative process even without actual objects in this type of art form than in the visual arts.…”
Section: In Uence Of Haiku Creation On the Aesthetic Evaluation Of Ha...mentioning
confidence: 99%
See 1 more Smart Citation